THE ROLE OF ONLINE MEDIA AS A SUPPORTER OF DEVELOPMENT TANJUNG RAJA LOCAL TOURISM - DAUD, ROSY FEBRIANI; Suryanti, Poppy; Laras Ati, Henny Dewi (Journal of Public Relations and Digital Communication (JPRDC), 2025)
Social media, where almost everyone has an account, is sometimes still separated from the creative economy entrepreneur segment, even though if we look closely at almost all times and places, everyone is familiar with social media starting from Facebook, Twitter, Instagram and other social media, but in reality there are still many entrepreneurs who are less focused on this situation. Online media plays a very important role in effective promotion and conveyance of information, especially as a supporter of local tourism development in the very promising digital era. In accordance with the potential presented by social media as a communication medium that can help tourism marketing in various marketing elements both in media and content, communication messages. Communication also plays a role in preparing message content that will be conveyed to the public, tourists about destinations, accessibility, human resources and tourism institutions. Considering that tourism is one of the regional resources that can provide the largest income for regional income and can help increase the human resources available in North Lampung. Online media plays a very active role in developing the local tourism potential of Tanjung Raja, North Lampung.